DIMENSI METRIK PADA GRAF Rn(q; r)m - Rendy Aditya Pratama; Narwen Narwen; Des Welyyanti (Jurnal Matematika UNAND, 2019)
The metric dimension of a connected graph G is the cardinality of minimum resolving set in graph G. In this research, how to find the metric dimension of Rn(q; r)m graph. Rn(q; r)m graph is constructing by subdivision operation on Lobster graph Ln(q; r). We obtain the metric dimension of Rn(1; 1)m graph for n > 2 is 2, the metric dimension of Rn(q; 1)m for n ≥ 2, q ≥ 2 is n(q − 1) and the metric dimension Rn(q; r)m graph for n ≥ 2, q ≥ 1 and r ≥ 2 is nq(r − 1).Kata Kunci: graf Rn(q; r)m , dimensi metrik, himpunan pemisah